Size effect on the deformation mechanisms of nanocrystalline platinum thin films. Issue 1 (December 2017) - Shu, Xinyu; Kong, Deli; Lu, Yan; Long, Haibo; Sun, Shiduo; Sha, Xuechao; Zhou, Hao; Chen, Yanhui; Mao, Shengcheng; Liu, Yinong
Abstract This paper reports a study of time-resolved deformation process at the atomic scale of a nanocrystalline Pt thin film capturedin situ under a transmission electron microscope. The main mechanism of plastic deformation was found to evolve from full dislocation activity-enabled plasticity in large grains (with grain sized > 10 nm), to partial dislocation plasticity in smaller grains (with grain size 10 nm < d < 6 nm), and grain boundary-mediated plasticity in the matrix with grain sizesd < 6 nm. The critical grain size for the transition from full dislocation activity to partial dislocation activity was estimated based on consideration of stacking fault energy. For grain boundary-mediated plasticity, the possible contributions to strain rate of grain creep, grain sliding and grain rotation to plastic deformation were estimated using established models. The contribution of grain creep is found to be negligible, the contribution of grain rotation is effective but limited in magnitude, and grain sliding is suggested to be the dominant deformation mechanism in nanocrystalline Pt thin films. This study provided the direct evidence of these deformation processes at the atomic scale.